The Effect of Using Mnemonics Strategies on Iraqi EFL Fine Arts Institute Students’ on Vocabulary Retrieval - Dr. Efad Abdul Jabbar Ghadban (Journal of College of Education, 2022)
أثر استخدام استراتيجيات التذكر (نيمونكس) في استرجاع المعاني لدى طلاب معهد الفنون الجميلة دارسي اللغة الإنكليزية لغة اجنبية
Keywords: Mnemonics, Strategies, Vocabulary, Retrieval